2012
DOI: 10.3390/biology1020439
|View full text |Cite
|
Sign up to set email alerts
|

Why Assembling Plant Genome Sequences Is So Challenging

Abstract: In spite of the biological and economic importance of plants, relatively few plant species have been sequenced. Only the genome sequence of plants with relatively small genomes, most of them angiosperms, in particular eudicots, has been determined. The arrival of next-generation sequencing technologies has allowed the rapid and efficient development of new genomic resources for non-model or orphan plant species. But the sequencing pace of plants is far from that of animals and microorganisms. This review focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 104 publications
0
110
0
Order By: Relevance
“…Our repeat DNA analysis suggested that ∼70% of the genome is repetitive (Table 2). Repeat sequences are difficult to assemble because high-identity reads can derive from different portions of the genome, generating gaps, ambiguities, and collapses in alignment and assembly 89 , 90 . This high repeat DNA content is likely to explain the relatively low scaffold N50 (17,908 bp), even though the sequencing depth exceeds ×100.…”
Section: Resultsmentioning
confidence: 99%
“…Our repeat DNA analysis suggested that ∼70% of the genome is repetitive (Table 2). Repeat sequences are difficult to assemble because high-identity reads can derive from different portions of the genome, generating gaps, ambiguities, and collapses in alignment and assembly 89 , 90 . This high repeat DNA content is likely to explain the relatively low scaffold N50 (17,908 bp), even though the sequencing depth exceeds ×100.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the biosynthetic pathways and mode of regulation of these compounds in non-model plants, including T. govanianum is difficult due to the lack of genomic information. However, the advent of NGS based high throughput transcriptome sequencing has aided to circumvent the difficulties in such plants3839. NGS approach has been successfully utilized to elucidate key genes and regulators of complex biosynthetic pathways in a number of non-model plants.…”
Section: Discussionmentioning
confidence: 99%
“…When the average GC content was lower than 30%, it will cause the significantly affect in genome sequence quality, and the influence on accuracy larger than integrity. The GC content proportions in the CSG plants were content with the previous reports in mammalian [57], [58], the moderate GC content will not improve the difficult of genome sequencing, and not affect the genome short reads assemble, gene prediction from the genome sequences.…”
Section: Resultsmentioning
confidence: 56%